Tow-components system: a molecular dialogue between ruminal bacteria and feed particles (forage plants) - Galicia Jiménez, Mónica Marcela (2017)
The ability to adapt rapidly to changes in the environment is one of the main characteristics of the bacterial cell. The rumen is a highly dynamic environment, and none of the changes are permanent due to the various microbial species found in the rumen. Signal transduction networks are information processing pathways that recognize various physical and chemical stimuli, amplification, signal processing, and trigger responses of the bacterial cell. The aim of the present review is to show the importance of these two component systems in rumen bacteria, because it is based on the knowledge of the principles governing the bacterial population communication, its main interactions and products of metabolism, we can approach the manipulation of Ruminal fermentation to improve animal health, productivity and food safety.